Tropical atmospheric boundary layer preliminary measurement - 380966 Karunakumar R. Ramasamy (Sekudai : UTM, 1993)
The knowledge and understanding of atmospheric winds in the lower layers of the atmosphere heve increased in importance with the rapid development of various practical engineering uses. These includes the design of aircraft control systems and runaways, the wind load upon structures, the utilization of wind as a source of energy and the flow of airborne particles in the lower strata of the atmosphere. the comprehension of wind behavior relies heavily upon the availability of a wind profile that is locally inclined. The main objective of this project is to produce a wind profile for the Tropical Atmospheric Boundary Layer consequently applicable as a wind data. This was done through direct measurements of various sites within Johor Bahru and with the aid of the modified ESDU 85003 program. Additionally since there are no similarly wind profile reference data in Malaysia, this project also serves as an initial investigation and a future guideline that lays the groundwork for future refinement of a wind profile reprensentative of Malaysia and it's local requirement. This will further progress to a wind profile of the Tropical Atmospheric Boundry Layer. Through out this project, direct full scale measurements were carried out within the constraints of this project and in modyfying the ESDU program into an executable file utilizing the QuickBasic language. The conclusions arrived at indicates that this project did not have the necessary hardware to successfully obtain the desired wind profile of thepreliminary measurements for the heights above te surface layer and thus heavily relied upon the ESDU program to achieve that particular specification. Nevertherless the remaining heights below the surface layer was achievable through direct measurements at the sites in concern. besides, during the determination of wind profile it was discovered that certain input parameters for the program relied upon local landscaping and weather condition which is not representative of Malaysia. further efforts to correct this error failed due to the lack of technical data. Finally, this research has provided the preliminary study into the methodology of measuring wind speeds for various heights at a particular site. It alsohighlighted the problems encountered and presented possible solutions of them. Reasonable assumptions have also been put forward to solve the problems and suggestions were made to enhance the efectiveness and accuracy of future work in thisfield.